Steady-state of azathioprine during initiation treatment of pediatric inflammatory bowel disease - Pozler, O; Chládek, J; Malý, J; Hroch, M; Dědek, P; Beránek, M; Krásničanová, P (Journal of Crohn's & colitis, 2010)
BACKGROUND AND AIM: Azathioprine (AZA) has a slow onset of action in treatment of pediatric inflammatory bowel disease (IBD). It is anticipated, that this delay correlates to the kinetics of 6-thioguanine nucleotides (6-TGN) accumulation. The aim of this study was to evaluate the time to steady state of 6-TGN concentration in red blood cells. METHODS: The inclusion criteria were: a) age 0-19 years b) IBD diagnosis c) AZA treatment initiation. High performance liquid chromatography was used for the 6-TGN analysis. Concentrations of metabolites were studied in weeks 0, 1, 2, 5, and 8 after beginning of treatment. RESULTS: The inclusion criteria were matched to 18 patients with IBD. The median time to steady state of 6-TGN was 55.3 days. The mean 6-TGN concentration at the steady state achieved 326 (SD 154) pmol/8.108 erythrocytes. High erythrocyte TPMT activity corresponds to the low steady state 6-TGN concentration and vice versa. This correlation reached statistical significance (p<0.01) for the dose expressed in mg per square meter of body surface area. CONCLUSION: The time to steady state of 6-TGN erythrocyte concentration is significantly shorter than would expected according to clinical observation describe earlier.
Keywords: Azathioprine; idiopatické střevní záněty; Immunosuppressive Agents; stupeň závažnosti nemoci; azathioprin; genotyp; Guanine Nucleotides; Genotype; mladiství; výsledek terapie; mužské pohlaví; methyltransferasy; Prospective Studies; Methyltransferases; dítě; Child; Child, Preschool; guaninnukleotidy; ženské pohlaví; imunosupresiva; předškolní dítě; prospektivní studie; Humans; Severity of Illness Index; Thionucleotides; Mercaptopurine; thionukleotidy; merkaptopurin; Inflammatory Bowel Diseases; Female; Adolescent; Treatment Outcome; lidé; Male